Deconstruction and Negative Theology. The Play between différance and onthological difference - Muñoz González, Diana María (Estudios de Filosofía, 2014)
Despite the frequent remarks made by Derrida about the serious mistake that it would be to take deconstruction as some kind of negative theology, his efforts to clearly distinguish them were not always very convincing. The important similarities between the rhetorical resources commonly used by both discourses, namely their employment of the via negationis, made it difficult to prove the distance. This paper tries to shed some light on the question by appealing to the notion of play, in the sense that negativity ruling deconstructive discourse might be seen, in contrast to the negativity of theological discourse, as a playfulness of writing that really matches the negativity of Being.